Comparative genetic analysis of VP4, VP1 and 3D gene regions of Enterovirus 71 and coxsackievirus A16 circulating in Malaysia between 1997-2008 - Chan, Y.F.; Wee, K.L.; Chiam, C.W.; Khor, C.S.; Chan, S.Y.; Amalina, W.M.Z.W.N.; Sam, I.C. (2012)
Three genomic regions, VP4 capsid, VP1 capsid and 3D RNA polymerase of human enterovirus 71 (EV-71) and coxsackievirus A16 (CV-A16) were sequenced to understand the evolution of these viruses in Malaysia. A total of 42 EV-71 and 36 CV-A16 isolates from 1997-2008 were sequenced. Despite the presence of many EV-71 subgenotypes worldwide, only subgenotypes B3, B4, B5, C1 and C2 were present in Malaysia. Importation of other subgenotypes such as C3, C4/D and C5 from other countries was infrequent. For CV-A16, the earlier subgenotype B1 was replaced by subgenotypes B2a and the recent B2c. Subgenotype B2a was present throughout the study while B2c only emerged in 2005. No genetic signatures could be attributed to viral virulence suggesting that host factors have a major role in determining the outcome of infection. Only three EV-71 B3 isolates showed non-consistent phylogeny in the 3D RNA polymerase region which indicated occurrence of recombination in EV-71. High genetic diversity was observed in the Malaysian EV-71 but Malaysian CV-A16 showed low genetic diversity in the three genomic regions sequenced. EV-71 showed strong purifying selection, but that occurred to a lesser extent in CV-A16.